Kamala Harris’s Convincing Strategies in Her First Presidential Nomination Speech: A Speech Act Analysis - Ihsani, Kayla Najmi; Handayani, Tuty (Universitas Gadjah Mada, 2025)
This research investigates the convincing strategies in Kamala Harris’s first speech for the 2024 United States presidential election. It classifies the assertive speech act used to convince the audience. Utilizing Searle and Vanderveken’s theory (1985), a qualitative method was applied. The data were collected through documentation techniques, including watching the speech, identifying relevant utterances, and organizing them on the data cards. The analysis identified 24 utterances from 3,306 words classified into nine categories of assertive acts: claim, inform, assure, admit, predict, criticize, insist, remind, and boast. The most frequently used act was boast (5 instances) emphasized her positive track record. This was followed by criticize (4 instances) aimed at offering better policy alternatives. Both assure (3 instances) and inform (3 instances) used to emphasize her personal background. Other acts that appear (2 instances) were claim, insist, remind, and predict. The least frequent was admit (1 instance) to expose policy mistakes. Notably, only the criticize involved indirect speech acts and non-literal meaning. The rest of the assertive acts are direct speech act and literal meanings. The findings suggest that Kamala Harris mostly uses boast to emphasize past achievements as convincing strategies for gaining audience trust in political campaigns.